Functional nanocrystal as effective contrast agents for dual-mode imaging: Live-cell sonoluminescence and contrast-enhanced echography - V. Vighetto; E. Pascucci; N.M. Percivalle; A. Troia; K.M. Meiburger; M.R.P. van den Broek; T. Segers; V. Cauda (Ultrasonics Sonochemistry)
In the context of molecular imaging, the present work explores an innovative platform made of lipid-coated nanocrystals as contrast-enhanced agent for both ultrasound imaging and sonoluminescence. At first, the dynamics of gas bubbles generation and cavitation under insonation with either pristine or lipid-coated nanocrystals (ZnO-Lip) are described, and the differences between the two colloidal systems are highlighted. These ZnO-Lip show an unprecedented ability to assist cavitation, which is reflected in enhanced sonoluminescent light emission with respect to the pristine nanocrystals or the pure water. Highly defined and sharp sonoluminescent images of cultured cells are indeed obtained, for the first time, when ZnO-Lip are used. Furthermore, ZnO-Lip were adopted as a nanosized agent for contrast-enhanced ultrasound imaging, i.e. echography, first in solutions, and then on ex-vivo tissues. A prolonged over time and bright imaging effect is observed when adopting the developed nanoparticles. Furthermore, their nanometric size and potential targeting with biomolecules would allow ease extravasation and tissue or even cell penetration, achieving enhanced-contrast imaging. Finally, the stimuli-responsive therapeutic applications of ZnO-Lip against tumors is overviewed, aiming to achieve a fully theranostic approach.